2017
DOI: 10.1111/sms.12874
|View full text |Cite
|
Sign up to set email alerts
|

Acute effect of running exercise on physiological Achilles tendon blood flow

Abstract: Sonographically detectable intratendinous blood flow (IBF) is found in 50%-88% of Achilles tendinopathy patients as well as in up to 35% of asymptomatic Achilles tendons (AT). Although IBF is frequently associated with tendon pathology, it may also represent a physiological regulation, for example, due to increased blood flow in response to exercise. Therefore, this study aimed to investigate the acute effects of a standardized running exercise protocol on IBF assessed with Doppler ultrasound (DU) "Advanced dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 37 publications
2
19
0
1
Order By: Relevance
“…After stepwise, multivariate, Cox proportional hazards model building for the development of AT, the final model included the variables sex, increase in blood flow after running, timing of blood flow measurements, and foot posture. The timing of blood flow measurements and foot posture were included as confounders in the analyses since previous studies showed that the Achilles tendon blood flow after activity had a fast increase followed by a quick recovery to baseline 43 and since recent studies confirmed the relationship between foot pronation and Achilles tendon blood flow. 22,52 The results of the multivariate Cox regression analysis and the strength of the predictive values are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…After stepwise, multivariate, Cox proportional hazards model building for the development of AT, the final model included the variables sex, increase in blood flow after running, timing of blood flow measurements, and foot posture. The timing of blood flow measurements and foot posture were included as confounders in the analyses since previous studies showed that the Achilles tendon blood flow after activity had a fast increase followed by a quick recovery to baseline 43 and since recent studies confirmed the relationship between foot pronation and Achilles tendon blood flow. 22,52 The results of the multivariate Cox regression analysis and the strength of the predictive values are presented in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…A small amount of IBF at rest has been suggested to be of physiological nature (Boesen et al, 2006a(Boesen et al, ,b, 2012. Moreover, IBF has been found to increase in response to tendon loading exercise (Boesen et al, 2006a,b;Fahlström and Alfredson, 2010;Sanz-López et al, 2016;Risch et al, 2018a) assuming a physiological metabolic reaction visualized due to increased flow velocity and/or volume in preexisting vessels (Boesen et al, 2006a(Boesen et al, ,b, 2012Risch et al, 2018a). In summary, detectability of IBF itself cannot be considered a pathological finding anymore (Boesen et al, 2006b(Boesen et al, , 2012Risch et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Then again, the amount of training hours has also been associated with an increased risk of developing Achilles tendinopathy (Knobloch et al, 2008). An acute increase in amount of sonographic detectable intratendinous vessels following exercise has been suggested to represent elevated blood flow in preexisting vessel beds, rising above the sensitivity threshold of Doppler ultrasound (Boesen et al, 2006b;Risch et al, 2018a). Other studies, however, have found contradictory effects of exercise on detectable IBF in terms of persisting, decreased (Malliaras et al, 2012) or absent blood flow (Pingel et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathologies of the foot and ankle involving the AT are a common orthopedic problem, mostly encountered among athletes and older adults (Beitzel et al, ; Yilmaz et al, ; Gärdin et al, ; Revak et al, ; Docking et al, ; Risch et al, ; Wengler et al, ). Several factors such as age and sex could account for this heterogeneity in the population.…”
Section: Introductionmentioning
confidence: 99%